2015
DOI: 10.1136/thoraxjnl-2014-206480
|View full text |Cite
|
Sign up to set email alerts
|

The prospective evaluation of the TB strain typing service in England: a mixed methods study

Abstract: To reduce costs, improve efficiency and increase effectiveness, we recommend changes to the TB-STS, including discontinuing routine cluster investigations and focusing on reducing diagnostic delay across the TB programme. This evaluation of a complex intervention informs the future of strain typing in the era of rapidly advancing technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Calculating the probability of developing disease from Erkens et al 7 rather than Sloot et al 24 does not qualitatively change the cost-effectiveness results (not shown). Using utility scores used by Mears et al 23 instead of those used by Jit et al 33 leads to a slight decrease in cost-effectiveness (online supplementary appendix part 6). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculating the probability of developing disease from Erkens et al 7 rather than Sloot et al 24 does not qualitatively change the cost-effectiveness results (not shown). Using utility scores used by Mears et al 23 instead of those used by Jit et al 33 leads to a slight decrease in cost-effectiveness (online supplementary appendix part 6). …”
Section: Resultsmentioning
confidence: 99%
“…The introduction in 2017 of whole genome sequencing (WGS) in the UK39 may also affect our conclusions. While a study of the current strain typing service found no impact on contact tracing,23 it is plausible that faster turnaround times and improved targeting available with WGS may affect contact tracing yields.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…128 However, as described by the routine strain typing service in the UK, the effect of molecular epidemiological data on patient care and public health response might not be useful if those data are not reported and acted upon quickly. 153 To achieve this, major technical and systems barriers must be overcome, including the strengthening of information technology systems to facilitate timely capture, export, and potentially automated analysis of complex data, such as in web-based systems; 148 linking molecular data to key epidemiological data (eg, geographical location); improving local scientific capacity; and providing decision makers with sufficient autonomy and resources to act in response to such data.…”
Section: Next-generation Molecular Epidemiologymentioning
confidence: 99%